The modernization of cil law institutions : civil liability, property and contract - Woolcott Oyague, Olenka; Monje Mayorca, Diego Fernando; Peláez Hernández, Ramón Antonio; Comandé, Giovanni; Morales Hervias, Rómulo (Bogotá : Universidad Católica de Colombia, 2019)
This work analyzes the treatment and contributions of Latin American las to specifics problems that are the object of continuous discussion in the doctrine and jurisprudence. To this end, the authors identify as principal issues of concerns: strict liability for hazardous activities in Colombian jurisprudence and in European tort law, the methods of property trasnfer of merchandise in international trade, and contract withdrawal in European and American civil codes.
The choice of a comparative study approach is due the innovative proposals in contract and tort law adopted in some of the most important harmonization documents of European law that hace been published since the middle of the twentieth century. These erve as reference sources for Latin American academics who seek to project the reach and evolution of contract and liability law within the Roman-Germanic tradition, as related to the current needs of Latin American law.
Thus, some of the civil liability problems this research book examines related to property and contract reveal the breadth and detail of their treatment, in order to propose an enriching debate to visualize a general perspective of its morphology and treatment.
1. Toward a reconstruction of strict liability law through colombian jurisprudence. 2. Presumption in the contex of civil responsibility and their application colombian jurisprudence. 3. The method to transfer ownership of mechandise in international trade. 4. European and law of civil liability. 5. The right to withdrawaal due to breach of contract in Eropean and South American civil codes.
Incluye bibliografía.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2022. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Civil law; Derecho civil; Responsabilidad civil; Contratos